Meningkatkan Karakter Gotong Royong Peserta Didik dalam Pembelajaran PAKBP dengan Model PBL Fase C Kelas V di SDN 23 Periang - Christine Yossy Meinarty; Fr. Wuriningsih; Budi Hartono (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
This research aims to describe the extent to which the application of the Problem Based Learning (PBL) model in PAKBP subjects can improve the mutual cooperation character of class V Phase C students at SDN 23 Periang, Kayan Hilir District, Sintang Regency. This type of research is Classroom Action Research (PTK), with two cycles, namely cycle 1 and cycle 2. The activity stages are planning, implementation, observation, analysis and reflection which are carried out face to face. The research is entitled